Internal and vendor employees' unethical behaviors in the supply chain: the case of India. Issue 1 (9th October 2019) - Yun, Gawon; Ebrahimpour, Maling; Bandyopadhyay, Prabir; Withers, Barbara
Abstract : Purpose: The purpose of this paper is to examine the impact of a corporate ethical policy, such as a code of ethics, on the unethical behavior of internal and vendor employees in the supply chain in India. It also aims to find whether International Standards Organization (ISO) certification of vendors affects the result and any significant relationship between management commitment and unethical behavior can be supported by the findings as well. Design/methodology/approach: Empirical analyses were conducted on a survey consisting of 43 questions comprising 181 valid responses. Multiple regression analysis that includes four independent variables – code of ethics, management commitment, supply chain principles and personal values taking unethical behavior as dependent variable – was used to find the significance of the relationship. Findings: The implementation of a code of ethics, management commitment, supply chain principles and personal values all have a negative association with unethical behavior. Personal values, measuring a firm's financial aspects for non-compliance to ethical behavior, have a positive association with unethical behavior. The relationships of top management commitment, personal values with internal employees' unethical behavior are significant. The significant relationship between management commitment and unethical behavior can be supported by the findings as well. It was also found that ISO certificates and firm size as the control variables did not have any effect on the relationship between the independent variables and unethical behavior. The analysis also shows that ISO 26000 certificate, the international standard for socially responsible operations, does not impact this relationship. Research limitations/implications: Measuring substantial managerial effort for corporate social responsibility (CSR) practices by asking questions like, "how committed employees think top management is to social responsibility, " may not fully measure substantial managerial effort for CSR practices. To improve the results of the current study, future research can use the CSR index or disclosure as a measure to better reflect management commitment and practice for social responsibility. Second, the current study is limited to measuring how many occurrences of unethical behavior are witnessed by employees instead of what specific unethical behavior is more often witnessed. Considering India has the second largest population in the world, 181 responses may not represent the true practices in the business environment in India for generalization. Practical implications: The findings suggest that management should put more of an emphasis on improving the commitment of upper-level managers to decrease the overall unethical practices of their employees. The study finds that employees' personal values influence their ethical behavior. Therefore, communications and training of employees at all levels should emphasis on improving personal values. Social implications: Businesses should influence academics to incorporate personal value building in course curricula. The Indian CSR law should incorporate the holistic view of CSR taking care of needs of all stakeholders under the provision of the regulation. In 2015, India became the first country in the world to legislate CSR practices in corporations but it misses the opportunity to sensitize the management and employees on ethical practices as it mainly identified philanthropic expenses as mandatory CSR spending and silent on ethical business practices. Originality/value: The present study contributes to the literature by bringing supply chain context to the effect of different factors on unethical behaviors and interaction of internal and vendor firms in terms of ethical practices. There are several studies on business ethics in different countries including China, but in the case of India similar studies are not much. The present study fills the gap.